#stopasianhate Anti-Racism Actions on Social Media Twitter: A Critical Discourse Analysis - Haliza, Nur; Triyono, Sulis (Humanus, 2022)
This study aims to describe the trending topic #stopasianhate on Twitter using a qualitative approach. The type of research conducted is descriptive-qualitative research that takes data on tweets with the hashtag #stopasianhate. The theory used as the basis for the analysis is the theory of Teun A. van Dijk with a discourse analysis model that includes three stages, namely (1) text structure (2) social cognition, and (3) context. In the analysis of the structure, the results show there is a form of social movement in the form of rejection and resistance to the actions of violence and racism accepted by people of Asian descent in America. This is reinforced by the results of the analysis macrostructure, superstructure, and microstructure which shows there is support from Twitter users to stop acts of violence and racism. In the analysis of social cognition, it was identified based on the results of the interpretation of individuals who used tweets with the hashtag #stopasianhate on Twitter. At the level of the social context, it was found there was a critique of people who committed acts of racism against Asians and it is hoped that this movement can awaken and increase one's concern for others.